2012
DOI: 10.1175/jhm-d-11-041.1
|View full text |Cite
|
Sign up to set email alerts
|

Probability Distribution of Precipitation Extremes for Weather Index–Based Insurance in the Zhujiang River Basin, South China

Abstract: In a changing climate, understanding the frequency of weather extremes is crucial to improving the management of the associated risks. The concept of weather index-based insurance is introduced as a new approach in weather risk adaptation. It can decrease the vulnerability to precipitation extremes that cause floods and economic losses in the Zhujiang River basin. The probability of precipitation extremes is a key input and the probability distribution of annual precipitation extremes is analyzed with four dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 33 publications
0
21
0
3
Order By: Relevance
“…As mentioned in the introduction, many distributions have been used in return period estimations (Park et al, 2001;Öztekin, 2007;Su et al, 2009;Fischer et al, 2012). The selection of only five distributions is one of the primary limitations of the 5 current study.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…As mentioned in the introduction, many distributions have been used in return period estimations (Park et al, 2001;Öztekin, 2007;Su et al, 2009;Fischer et al, 2012). The selection of only five distributions is one of the primary limitations of the 5 current study.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Fischer et al . () analysed the precipitation extremes in the Pearl River with four distribution functions and showed that on basin scale, the generalized extreme value (GEV) is the most reliable and robust distribution for estimating precipitation indexes for an index‐based insurance programme in the Pearl River Basin. Ding et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many scholars apply statistical distributions to make further research on extreme precipitation events. Fischer et al (2012) analysed the precipitation extremes in the Pearl River with four distribution functions and showed that on basin scale, the generalized extreme value (GEV) is the most reliable and robust distribution for estimating precipitation indexes for an index-based insurance programme in the Pearl River Basin. Ding et al (2009) fitted the extreme rainfall in summer in China by generalized Pareto (GP) and found the excellent simulation effects of the statistical model.…”
Section: Introductionmentioning
confidence: 99%
“…The Wakeby distribution has been mainly used for modeling extreme events and in the most cases for hydrology studies, for example researches developed by [40][41][42][43][44][45]. The distribution has five parameters, more than the most used ones.…”
Section: Discussionmentioning
confidence: 99%